Navigating Artificial Intelligence Integration in Contemporary Da'wah through Islamic Communication Ethics Principles - Hsb, Hamdi Maulana; Lahmuddin; Zainun (Institut Agama Islam Sunan Giri Ponorogo, 2026)
The rapid development of digital technology, particularly Artificial Intelligence (AI), has significantly transformed communication practices, including the field of da'wah. This study aims to examine the integration of Islamic communication ethics in the utilization of AI for da'wah in the digital era. This research employs a qualitative, sociological design to understand the social dynamics, communication patterns, and ethical implications of AI use in contemporary da'wah activities. The analysis is grounded in the perspectives of Islamic communication ethics and the sociology of communication, which emphasize the relationship among technological development, religious communication, and social values. Data were collected through a literature review of scholarly publications related to Islamic communication ethics, digital da'wah, and Artificial Intelligence. The findings indicate that AI offers significant opportunities to expand the reach, efficiency, interactivity, and personalization of da'wah messages. However, its implementation also raises sociological and ethical concerns, including the spread of misinformation, the distortion of religious messages, algorithmic bias, the weakening of religious authority, and the potential decline in humanistic interactions between da'i and mad'u. In this context, Islamic communication ethics, reflected in the principles of qaulan sadidan (truthfulness), qaulan layyinan (gentleness), qaulan balighan (effectiveness), and tabayyun (verification), offer an important normative framework for ensuring ethical and responsible AI-based da'wah practices. This study contributes to the field of Islamic Communication and Broadcasting by enriching the discourse on digital da'wah, communication ethics, and the sociological implications of emerging technologies in religious communication. The study concludes that integrating Islamic ethical values with technological innovation is essential for maintaining the effectiveness, credibility, and moral integrity of da'wah in the digital age, where AI serves as a supporting medium rather than a substitute for human religious guidance.